CO2 reduction on Cu/C used as a cathode in a polymeric electrolyte reactor - Fuel cell type. (19th January 2022) - Lima, Mariana; Godoi, Camila M.; Santos, Monique C.L.; Nandenha, Julio; Neto, Almir O.; De Souza, Rodrigo F.B.
Abstract: CO2 is one of the leading greenhouse gases, so studies that turn this gas into higher value-added products, that function as simpler and cheaper hydrogen stores, as an alcohols, are extremely important. In this work we using a polymeric Electrolyte Reactor– fuel cell type supplied with H2 on platinum anode and dry CO2 in the cathode with a copper-carbon electrocatalyst. Copper nanoparticles supported on carbon Vulcan XC72 were produced by the sodium borohydride reduction method. The XRD revealed the presence of two different phases, CuO and Cu2 O. In addition, the TEM images revealed agglomerates presence. The water, formaldehyde, methanol, methane, formic acid, dimethyl ether, oxalic acid, dimethyl carbonate, and ethylene-glycol were observed by differential mass spectroscopy on line with the reaction and the onset potential for each product and these results were confirmed by infrared spectroscopy – ATR-FTIR setup. This work showed the mapping CO2 reduced compounds for onset potential proposing some contributions to the literature. Graphical abstract: Image 1 Highlights: CO2 RR on polymeric electrolyte reactor. Mapping CO2 reduced products for onset potential and tracing a reaction pathways. CO2 RR on Cu/C to C1–C2 products.